Cutaneous metastasis heralding invasive ductal carcinoma of the breast in a 33 year old patient - Crystal R. Lenz; Kirk A. Middleton (Our Dermatology Online, 2016)
Cutaneous metastatic carcinoma is an unusual clinical finding, with an estimated overall incidence of 5.3%. While it is more frequently found in association with breast cancer than visceral malignancies, it is rarely identified until late in the course of the disease, and quite uncommonly as the heralding manifestation of the underlying malignancy. Because of the prevalence in breast cancer, it is important for primary care clinicians and dermatology specialists alike to be aware of this potential presentation, and able to identify such cutaneous manifestations both in the post breast reconstruction patient as well as the rare patient in which cutaneous manifestations arise as the first indication of the underlying malignancy. This case presentation is an example of the latter situation, with infiltrating ductal carcinoma (IDC) of the breast presenting as a small erythematous skin nodule in a young healthy patient with no known risk factors for breast cancer and no initial radiographic abnormalities to indicate presence of the underlying malignancy at the time of dermatologic evaluation. A review of the relevant literature is included to highlight key concepts.